Talent transfer in sport: Expert coaches` insights - Dickinson, R. K.; Mallett, C. J.; Gulbin, J.; Weissensteiner, J. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Talent transfer (TT) is a relatively newly discussed term appearing in academic literature (e.g., Vaeyens et al., 2009), referring to the idea of athletes "swapping" sports, or being "recycled" within a sport system. As such, TT as a distinct phenomenon is relatively under-researched in either theoretical or empirical published literature compared to many other approaches to sport talent identification and development (TID&D). Despite little research, the strategy has been used on a systematic level by a number of countries. The current study aimed to understand TT in more depth through rigorously gathering the expert knowledge of coaches who have undertaken the "transferring" of athletes within the Australian sport system. Method: 13 expert coaches (10 male) experienced in attempting to "transfer" athletes participated in semi-structured interviews regarding their background, involvement, processes, and experiences in TT. Interviews were conducted face-to-face (11), and by telephone (2), averaging 92 mins. Interviews were audio recorded and transcribed, memberchecked, and coded using Nvivo9 software, checking for inter-coder agreement amongst researchers. Data were organised into meaning units, higher and lower order themes, as per qualitative research methodology published by Côté et al (e.g., 1993), and also represented in the form of a model. Results: There were conceptually varied definitions of TT within the sample. Coaches gave insights from their experiences into broad themes such as: transferable and non-transferable elements between sports, barriers and facilitators, coach skills and qualities, athlete qualities, possibilities and limits of TT, necessary support, and important considerations for TT. Considerations such as: the differences between sport cultures and environments, athletes` personal characteristics, squad dynamics, the importance of a clear and well structured program of training with realistic goals and expectations, respect for athletes` backgrounds, and adequate access to resources were key factors suggested for successful TT. Discussion: A multi-dimensional model of successful TT, including physical, mental, environmental, interpersonal, and structural considerations is proposed. Results are discussed in relation to conceptions of TT, implications for coaching practice and talent management by individual coaches and national sport systems, and the wider context of TID&D research. Limitations of the current study and future research areas are also discussed.